Trace element behaviour in acidic leachates (acetic, nitric and hydrochloric) from siliciclastic-carbonate rocks of the Upper Riphean Uk formation in the Southern Urals - Dub, S. A.; Cherednichenko, N. V.; Kiseleva, D. V.; Gorbunova, N. P.; Gulyaeva, T. Ya; Deryugina, L. K. (Litosfera (Ekaterinburg. Online), 2020)
Research subject. 14 samples of limestone and one sample of carbonate-siliciclastic rock from siliciclastic-carbonate deposits of the Upper Riphean Uk Formation (the Southern Urals) were studied. Methods . Mineral and chemical composition of the samples were determined; the main tool for detecting the concentrations of trace elements was the ICPMS method. X-ray diffraction analysis was carried out using a Shimadzu XRD-7000 diffractometer, the content of major (rock-forming) oxides in bulk samples was established by X-ray fluorescence spectrometry on the SRM-35 and Shimadzu XRF 1800 spectrometers. Microelement composition of bulk samples and acidic leachates obtained with using acetic (10%), nitric (36%) and hydrochloric (17%) acids was determined on a Perkin Elmer ELAN 9000 spectrometer. Results. The distribution of lithophile, rare-earth and a number of other elements (Sr, Ni, U) both in bulk samples and in acidic leachates was analyzed. The main carrier phases of these elements were revealed. Conclusions . 1. The use of any listed acids leads to the non-carbonate component entering the solution, including contamination of the “carbonate” leachates by lithophile elements. In particular, a transition Rb, Zr, Li, Th, Ti, Sc to leachates was noted. This process is most active in nitric and hydrochloric acids, less intensive in acetic acid. 2. Among the carriers of rare earth elements (REE) in the studied rocks are clays (1), accessory minerals (2), including phosphate-bearing grains, secondary carbonate phases represented by dolomite and, possibly (3), finely disseminated iron and manganese (oxy)hydroxides (4). It is assumed that the REE pattern in limestones is determined by the content of the epigenetic dolomite. The contribution of lanthanides bound in the sedimentary calcite crystal lattice in the total REE pattern is rather large only in relatively “pure” limestones. However, the use of acids with such concentrations did not allow to obtain a leachate, which the REE pattern with high probability corresponds to the distribution of REE in the Uk time seawater. But acetic acid is more effective for achieving this goal than the others. 3. In addition to Sr, sedimentary calcite also contains Ni and U.